Development and characterization of novel jGCaMP8f calcium sensor variants with improved kinetics and fluorescence response range - Tran, Oanh; Hughes, Holly J.; Carter, Tom; Török, Katalin (Frontiers in Cellular Neuroscience, 2023)
Genetically encoded biosensors for monitoring intracellular calcium changes have advanced our understanding of cell signalling and neuronal activity patterns in health and disease. Successful application of GCaMP biosensors to a wide range of biological questions requires that sensor properties such as brightness and dynamic range, ligand affinity and response kinetics be tuned to the specific conditions or phenomena to be investigated. Random as well as rational targeted mutations of such sensor molecules have led to a number of important breakthroughs in this field, including the calcium sensors GCaMP6f and GCaMP6fu. jGCaMP8f of the most recently developed generation is promising a step-change in in vivo imaging with further increased fluorescence dynamic range. Here, we critically examine the biophysical properties of jGCaMP8f and report development by rational design of two novel variants of jGCaMP8f. We developed jGCaMP8f L27A which has a 3-fold faster off-kinetics and jGCaMP8f F366H which shows a 3-fold greater dynamic range than jGCaMP8f, both in vitro and in HEK293T cells and HUVEC in response to ATP stimulation. Importantly, we demonstrate that the physiologically highly relevant Mg2+ not only majorly affects the kinetic responses of GCaMPs but also their brightness and fluorescence dynamic range. Finally, we discuss the importance of optimization of biosensors for studying neurobiology in the context of the novel variants of jGCaMP8f.